K-pop in Metro Manila: The mediating role of South Korean product evaluation on the causal relationship between degree of fandom and purchase intention - Canon, Hannah Chloe Nicole A. (Animo Repository, 2022)
Korean Pop Music has garnered tremendous popularity from thousands of fans around the globe. Despite the language barrier, Filipinos are no exception. It is undeniable that the Philippines is a growing market for Korean products and services, yet literature on consumer behavior of Filipino K-Pop fans remains underexplored. This study seeks to examine the extent of South Korean Product Evaluation as a mediator in the relationship between the Degree of Fandom and Purchase Intention of 400 Filipino K-Pop fans for K-Pop Related Korean Products. Through mediated regression analysis, this study revealed that sub-variables Perceived Quality and Perceived Value of South Korean Product Evaluation have mediating effects on the relationship between Degree of Fandom and Purchase Intention, suggesting that fans’ fanaticism affects their perceived quality and value, which then influences their purchase intention of K-Pop Related Korean Products. Recommendations were provided by the researchers for businesses, entrepreneurs, and marketers on how to incorporate K-Pop affiliations into business and communication objectives. Recommendations for the academe, future researchers and fans themselves, were also provided in light of the research findings.